Plan estratégico para la empresa de Electrodomésticos Fago Cía. Ltda. de la ciudad de Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos para el periodo 2016 - 2021 - Lució Choez, Viviana Carolina (2017)
The objective of the present thesis was to elaborate a strategic plan for the Company of Electrical Appliances "FAGO CÍA LTDA", of the city of Nueva Loja for the year 2016 - 2021, said contribution is synthesized in the elaboration of a strategic plan of marketing, through which it is foreseen to boost the processes of selling electrical appliances offering a better service. The methodological component used during the present investigative process was composed of the following methods: scientific method, inductive, deductive, statistical and analytical; Likewise, the following techniques were used: direct observation, interview and the survey. During the process of collecting data and other information necessary for the structuring of this work, there was a direct participation of 10 workers and the Manager of that company. The most important results of the investigation were the weighted matrix EFE, which reached 2.86, the total weighted value of the FFI matrix was 2.60, evidencing the need to develop strategies that contribute to attenuate the threats and weaknesses detected. With the valuable information obtained through the accomplishment of the respective external and internal analysis, the matrix of High Impact or Force Measurement was structured, whose crosses: FO - FA - DO - DA, arrived to be determined in the present project is to strengthen the strategic direction and promote the continuous improvement of FAGÓ Cía Ltda., with a value of $ 14.00 dollars, Raise the participation of the Company of appliances "FAGÓ" Cía. Ltda., in the market with a value of $ 2,300.00 dollars, implement a promotions plan to increase the client portfolio of $ 2,400.00 dollars and Potential development of the internal customer with a value of $ 1,379.00 dollars. The inclusion of the present strategic plan of marketing within the organic part of the company, demand of the economic delivery by its partners of the amount of $ 4,713.00 USD Finally, the proposal of the Strategic Plan for the company FAGO Ci. Ltda. Of the city of Nueva Loja